The Relationship Between the Tradition of Giving Honey to Newborns and Husband Support with Exclusive Breastfeeding: Hubungan Sosial Budaya dan Dukungan Suami dengan ASI Eksklusif - Destariyani, Elvi; Yuniarti; Yulyana, Nispi (JURNAL KEBIDANAN, 2024)
Exclusive breastfeeding coverage in Indonesia is 73.97%, while in Bengkulu Province exclusive breastfeeding coverage is 72.44%. This figure is still far from the national target of 80%. Support from various parties is needed to achieve the target of exclusive breastfeeding. This research aims to determine the socio-cultural relationship and husband's support with exclusive breastfeeding. This research has an analytical survey research design with a cross sectional approach. The population of all mothers who have babies aged 7 to 12 months with samples taken using the Lemeshow formula calculation resulted in 102 research respondents being mothers. Samples were taken using accidental sampling technique. Data were analyzed using the Chi Square test. The results of the research showed that a small number of respondents had a social culture that did not support exclusive breastfeeding, some respondents did not receive husband support in providing exclusive breastfeeding, and the majority of respondents did not exclusively breastfeed their babies. There is a socio-cultural relationship with exclusive breastfeeding p value = 0.001 and husband's support with exclusive breastfeeding p value = 0.038. It is hoped that health workers will provide information and motivation for exclusive breastfeeding and accompany mothers in the breastfeeding process to increase exclusive breastfeeding coverage in Bengkulu City.